The Genus Priotomis in Argentina (Hymenoptera, Ichneumonidae) - Charles C. Porter (Psyche: A Journal of Entomology)
The genus Priotomis (Townes, 1969, p. 292) was placed by its author in the subtribe Lymeonina of the ichneumonid tribe Mesostenini. While data provided by a study of the new species treated in this article do not controvert that placement it is well to emphasize that Priotomis shows a number of singularly aberrant characters unparalleled among other genera of its subtribe. For example, the presence of a series of teeth on the dorsal valve of the ovipositor tip recalls the Baryceratina rather than the Lymeonina, whereas the specialized, twisted mandibular apex is not found in any other mesostenine genus.